A major practicum report at the Tribu Davao Fruits and Preserves, 8 Camarin St., Riverside, Maa, Davao City - Edejer, Grace Paster (2009)
Southern Mindanao is the highest producer of fruits (by volume) in the Philippines. A considerable quantity o fruits is easily wasted since it is highly perishable thus processing is significant and it necessitates improving food safety and quality with due consideration to maximizing efficiency in the fruit processing sector. A major plant practice was conducted at Tribu Davao Fruits and Preserves, Maa, Davao City from November 2008 to December 2008 to study the plant operation and its implementation of integrated food control operations (GMP and SSOP and its preparation for HACCP. The practice involves observation of the entire operation including personnel, buildings and facilities, process and controls, equipment, and systems. It has been shown that the plant lack strict adherence to process parameters as set in the GMP and SSOP guidelines and that the plant needs to integrate quality control and quality assurance systems. The construction of the new laboratory brings about many potential research and development subjects such as enhancing the quality of processed macapuno, monggo, and ube. Improving the delivery system of the plant and reduction of product recalls by following standard procedures in packaging would increase efficiency. The findings suggest that the collaboration of the government (DOST) and fruit processors needs to be intensive to closely monitor GMP and SSOP implementation and it has an implication on including suppliers in the collaborative relationship
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2009
Keywords: Tribu Davao Fruits and Preserves; Tribu Davao Fruits and Preserves -- Maa, Davao City -- Philippines; Fruits; Fruit preserves; GMP (Good Manufacturing Practices; Food control operations; Food safety; Quality assurance systems; Food quality; Fruit preservation; Gelling mechanism; Gelling systems; Sothern Mindanao -- Philppines